2010
DOI: 10.1159/000319195
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis and Mapping of the <i>Sry </i>Gene in Species of the Subfamily Arvicolinae (Rodentia)

Abstract: The rodent subfamily Arvicolinae, which contains about 125 species, presents some interesting exceptions concerning Sry, the sex determining gene in mammals. In some species multiple Sry copies have been described on the Y chromosome and in the Iberian vole, Microtus cabrerae, several Sry sequences have been cloned and mapped not only on the Y but also on the X chromosome. Here we present a comparative analysis of Sry sequences from a total of 22 species. Our study demonstrates for the first time that for most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Mus sensu stricto , whereas the latter 2 are from different subgenera, Coelomys and Nannomys , respectively [Veyrunes et al, 2006]. These sequence similarities are equivalent to what is observed between 4 genera of North American voles [Acosta et al, 2010], but lower than between 6 African murid genera (97-100%) [Lundrigan and Tucker, 1997]. Hence, the similarity of nucleotide sequences within the genus Mus is comparable, if not lower, to those observed between closely related genera.…”
Section: Sequence Analyses Of the Sry Gene In The Genus Mussupporting
confidence: 58%
See 2 more Smart Citations
“…Mus sensu stricto , whereas the latter 2 are from different subgenera, Coelomys and Nannomys , respectively [Veyrunes et al, 2006]. These sequence similarities are equivalent to what is observed between 4 genera of North American voles [Acosta et al, 2010], but lower than between 6 African murid genera (97-100%) [Lundrigan and Tucker, 1997]. Hence, the similarity of nucleotide sequences within the genus Mus is comparable, if not lower, to those observed between closely related genera.…”
Section: Sequence Analyses Of the Sry Gene In The Genus Mussupporting
confidence: 58%
“…In contrast to most mammals, including the house mouse and human that possess a single copy of the Sry gene, multiple Y-specific copies have been reported in several other Mus species and some other rodents [Nagamine, 1994;Lundrigan and Tucker, 1997;Acosta et al, 2010]. Interestingly, among the mammals with multiple copies of this gene, a notable proportion concerns species with atypical sex determination systems ( Microtus cabrerae and M. oregoni in Bullejos et al [1997] and Acosta et al [2010]; Akodon sp.…”
Section: The Sry Gene In Male and Female M Minutoidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the upstream sequence we found a (TC) n microsatellite ( fig. 3 ), which is also present at the same position in the Sry genes of mouse [Washburn et al, 2001], Clethrionomys rufocanus , Eothenomys andersoni and Eothenomys smithii [Iwasa et al, 2000;Iwasa and Suzuki, 2002] and in all the species of Arvicolinae analyzed by our group [Acosta et al, 2010]. -X3Y-F81-1 ......................................................................................................... Aaz-X3Y-F81-3 .................................................................................................... -XY-F87-17 ..............................................................T..................A....................... Abo-XY-F100-19 ..............................................................T..................A.................. X3Y-F81-1 ..........G.............................................................................................. Aaz-X3Y-F81-3 .................................................................................................... -XY-F87-17 ........A..............................................................................................G. Abo-XY-F100-19 .................................................................................................... X3Y-F81-1 .................................................................................................... Aaz-X3Y-F81-1 ................................................................................................... Aaz-X3Y-F81-3 .............................................................................................. -XY-F100-19 ...............................TACTGAGTTTC.................................................... With respect to mouse Sry, it has been suggested that this microsatellite could be involved in the formation of a secondary structure that would reduce translational efficiency [Hacker et al, 1995].…”
Section: Resultsmentioning
confidence: 61%
“…Our results are consistent with the presence of several Sry copies in A. azarae and A. boliviensis individuals. The presence of several Sry copies has also been described in several murid rodents [Nagamine, 1994], in Rattus norvegicus [Turner et al, 2007], and in several Arvicolinae species [Bullejos et al, 1997[Bullejos et al, , 1999Acosta et al, 2010]. While it seems that all the Sry copies in R. norvegicus are transcribed and are probably functional [Turner et al, 2007], some copies of this gene are non-functional pseudogenes in species of Arvicolinae, since they possess several premature stop codons [Bullejos et al, 1997[Bullejos et al, , 1999Marchal et al, 2008].…”
Section: T Mmus-sry ----------------------------------mentioning
confidence: 93%